DAMPAK MEDIA SOSIAL TERHADAP PERILAKU DAN POLA INTERAKSI DI ERA DIGITAL - M Yunus M Yunus; Adinda Nabila Putri; Sintia Anggraini (LAP4B, 2026)
This Community Service (PKM) activity was held at SMA PGRI 2 Depok with the aim of providing education to students regarding the impact of social media use on social behavior and shifts in interpersonal interaction patterns in the digital era. The intense presence of social media in adolescents' lives often triggers a shift from face-to-face interaction to virtual interaction, which, if not managed wisely, can affect mental health, consumerist behavior, and the quality of real-world interpersonal communication. The activity used a qualitative Participatory Action Research approach delivered through polite, respectful language, comprising interactive lectures, focus group discussions (FGD), case studies on cyberbullying, FOMO, and phubbing, and screen-time tracking simulations. The results demonstrated a significant increase in students' understanding of the importance of limiting social media screen time, maintaining online communication ethics, and the formation of student digital ambassadors. Through this PKM activity, it is hoped that students of SMA PGRI 2 Depok can develop digital literacy skills and maintain balanced social interaction patterns to become an adaptive, smart, and positive-charactered younger generation in the digital era